The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/adfm.202112832
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Local Spin State and Band Structure in Ni3S2 Nanosheet for Improved Oxygen Evolution Activity

Abstract: The separate modulation of the adsorption of *O and *OOH is challenging in oxygen evolution reaction (OER), which results in a large overpotential and slow kinetics. To balance the adsorption of the two active species, here, a way to regulate the local spin state and band structure simultaneously in Ni3S2 nanosheets is reported. The adequate doping of W heteroatoms causes the electron depletion from the Ni active site, which modulates the spin state of eg electrons, weakening the adsorption of *O. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 49 publications
1
71
0
Order By: Relevance
“…Experimental and theoretical calculations have revealed that changes in the adsorption of oxygen-containing intermediates are key to rate limiting in catalytic reactions. 47 The hydrogenation of OH to water increased significantly in the Ti–N 4 –Gr/V 2 C and Cr–N 4 –Gr/V 2 C catalysts, which is not favorable for the ORR process. The hydrogenation *OH to H 2 O is the rate-determining step for Ti–N 4 –Gr/V 2 C, Cr–N 4 –Gr/V 2 C, Mn–N 4 –Gr/V 2 C, Fe–N 4 –Gr/V 2 C, Co–N 4 –Gr/V 2 C, Ni–N 4 –Gr/V 2 C, and Cu–N 4 –Gr/V 2 C. Among them, Ni–N 4 –Gr/V 2 C and Co–N 4 –Gr/V 2 C exhibited high ORR performance with theoretical overpotentials of 0.32 and 0.45 V, respectively; Co–N 4 –Gr/V 2 C showed a catalytic activity comparable to that of the Pt/C catalyst.…”
Section: Resultsmentioning
confidence: 92%
“…Experimental and theoretical calculations have revealed that changes in the adsorption of oxygen-containing intermediates are key to rate limiting in catalytic reactions. 47 The hydrogenation of OH to water increased significantly in the Ti–N 4 –Gr/V 2 C and Cr–N 4 –Gr/V 2 C catalysts, which is not favorable for the ORR process. The hydrogenation *OH to H 2 O is the rate-determining step for Ti–N 4 –Gr/V 2 C, Cr–N 4 –Gr/V 2 C, Mn–N 4 –Gr/V 2 C, Fe–N 4 –Gr/V 2 C, Co–N 4 –Gr/V 2 C, Ni–N 4 –Gr/V 2 C, and Cu–N 4 –Gr/V 2 C. Among them, Ni–N 4 –Gr/V 2 C and Co–N 4 –Gr/V 2 C exhibited high ORR performance with theoretical overpotentials of 0.32 and 0.45 V, respectively; Co–N 4 –Gr/V 2 C showed a catalytic activity comparable to that of the Pt/C catalyst.…”
Section: Resultsmentioning
confidence: 92%
“…Compared with the fresh NiS x , NiS x -R demonstrates weaker peaks ascribed to metal-sulfur bindings (Ni-S) at 162 eV (S 2 p 3/2 ) and 163 eV (S 2 p 1/2 ), and a stronger S-O peak at ~168 eV (Fig. 3h ), suggesting the surface oxidization during the CV activation 4 , 39 . Figure 3i shows the fitting peaks of Se 3 d at 55 and 54 eV, agreeing well with the chemical states of Se 3 d 3/2 and Se 3 d 5/2 .…”
Section: Resultsmentioning
confidence: 99%
“…Producing H 2 through a green and sustainable way plays a vital role in the upgrading of energy sector and the fighting of global warming, [1,2] Electrocatalytically water splitting holds encouraging prospect for the production of hydrogen, where electrocatalysts are required to boost the electron-proton coupled transportation. [3][4][5][6][7] Transition metals and their complexes in the d-electron area of the periodic table constitute a large portion of the catalyst library for the hydrogen evolution reaction (HER), [8][9][10][11][12][13][14] taking advantage of the versatile interaction between the empty d band…”
Section: Introductionmentioning
confidence: 99%